The Design of a Semi-Prefabricated LVL-Concrete Composite Floor - David Yeoh; Massimo Fragiacomo (Advances in Civil Engineering)
This paper describes the design of a novel semi-prefabricated LVL-concrete composite floor that has been developed in New Zealand. In this solution, the floor units made from LVL joists and plywood are prefabricated in the factory and transported to the building site. The units are then lifted onto the supports and connected to the main frames of the building and to the adjacent units. Finally, a concrete topping is poured on top of the units in order to form a continuous slab connecting all the units. Rectangular notches cut from the LVL joists and reinforced with coach screws provide the composite action between the concrete slab and the LVL joists. This system proved to be an effective modular solution that ensures rapid construction. A design procedure based on the use of the effective flexural stiffness method, also known as the “gamma method” is proposed for the design of the composite floor at ultimate and serviceability limit states, in the short and long term. By comparison with the experimental results, it is shown that the proposed method leads to conservative design. A step-by-step design worked example of this novel semi-prefabricated composite floor concludes the paper.